PENGARUH KOMPETENSI PERANGKAT DESA, SISTEM PENGENDALIAN INTERNAL DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI KECAMATAN BATANG TUAKA KAB. INDRAGIRI HILIR - MELASARI, RANTI; SURYANI, SURYANI; INDRIYANI, PUTRI (Fakultas Ekonomi Universitas Islam Indragiri, 2023)
This research aims to determine the influence of village apparatus competency, internal control system and community participation on the accountability of village fund management in Batang Tuaka District, Indragiri Hilir Regency. This research was conducted at the Batang Tuaka District Village Apparatus. The types and sources of data in this research were primary data and secondary data. The population in this study was village apparatus in Batang Tuaka District. The data collection techniques used were interviews, questionnaires and literature studies. The research sample was village apparatus in Batang Tuaka District, totaling 39 respondents. The data analysis technique used was data instrument testing which consists of validity and reliability tests, multiple linear regression, coefficient of determination test, t test and f test. The research results show that partially the Competence of Village Apparatus, Internal Control Systems and Community Participation influence the Accountability of Village Fund Management of Village Apparatus in Batang Tuaka District. Then the research results simultaneously show that Competence of Village Apparatus, Internal Control System and Community Participation together influence the Accountability of Village Fund Management of Village Apparatus in Batang Tuaka District.